The Influence of Extroversion Personality towards EFL Learners' Writing Skills - Wira Kafryawan (LPPM Universitas Lancang Kuning. Pekanbaru. Indonesia, 2020)
This study aims at finding out whether or not there is a significant correlation between EFL learners' extroversion personality and their writing skills. Correlational research is used as a type of research method used in the study involving observing two variables consisting of extroversion personality and writing skills to establish a statistically corresponding relationship of them. To collect the samples, the sampling technique used is Saturated Sampling which means the technique of determining the sample when all members of the population are used as samples. Therefore, the samples are 50 EFL learners as respondents. The study was employed at Pohuwato University, Faculty of Teacher Training and Education, English Education Department. By using EPI questionnaire, it is clear to find out the personality of the respondents whether the learner is introvert or extrovert. Furthermore, writing skills are assessed by using criteria of writing test by Heaton. Both extroversion data and writing skills data are quantifiable data. The data were then analyzed by Pearson product-moment. The findings showed that there was a medium correlation between EFL learners' extroversion personality and their writing skills. It can be concluded that extroversion personality gives a medium influence to EFL learners writing skills. In other words, extrovert learners' tent to show good writing skills. Further studies are expected to elaborate more specifically about extroversion personality and writing skills.